EFFECT OF METHYL-Î’-CYCLODEXTRIN COMPLEXATION ON THE HYPOGLYCEMIC AND HYPOLIPIDEMIC EFFECTS OF KHELLIN: EXPERIMENTAL STUDY - Abousamra, Mona M.; Basha, Mona; Awdan, Sally El; Ismail, Nasser S. M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present work tackled the development and evaluation of inclusion complex of khellin (KH) and methyl-Î²-cyclodextrin (MÎ²CD). In addition, it tested its possible hypoglycemic and hypolipidemic effects. Methods: Inclusion complexes of KH-MÎ²CD in the presence of water-soluble polymer were prepared by freeze drying (FD), co-evaporation (EV) and kneading methods (KN). The selected ternary complex was characterized by Fourier transform infrared spectrophotometry (FTIR), x-ray diffractometry (XRD), differential scanning calorimetry (DSC) and scanning electron microscopy [1]. Assessment of the hypoglycemic effect of the selected ternary complex versus the standard drug metformin was studied. Two different doses of the ternary complex were administered orally to streptozotocin (STZ)-induced type 2diabetic rats. Their hypoglycemic and hypolipidemic effects were evaluated by measuring the fasting blood glucose level (BGL), total cholesterol (TC) and triglycerides levels (TG) along the study period. Results: The FD complex showed the highest drug dissolution rate. All the performed characterization analysis confirmed the formation of a KH-MÎ²CD inclusion complex. The in vivo study declared that both doses showed a marked hypoglycemic and hypolipidemic effects compared to metformin. Conclusion: In conclusion, this study points for the first time that the complexation of KH with MÎ²CD could notably improve the dissolution rate and hence the bioavailability of KH. Moreover, this study demonstrated that this compound has a hypoglycemic and hypolipidemic effect. Thus, it can be a promising natural supportive treatment in type 2 diabetes mellitus (T2DM).Â